Perspectives of multidisciplinary healthcare providers in elderly daycare centres: Challenges, opportunities and impacts on geriatric care in Chiangrai Municipality, Thailand - Paralee Opasanunt; Panitsara Leekuan (PLoS ONE, 2025)
The global surge in the ageing population has intensified pressure on healthcare delivery systems, leading to a heightened demand for elderly daycare services. This demographic shift necessitates innovative approaches to meet the complex needs of older adults, including expanding community-based care options. Elderly daycare centers play a crucial role in comprehensive geriatric care by offering services. Understanding how healthcare providers experience their work in Elderly Daycare Centres is essential for improving both service quality and staff preservation. This study seeks the experiences of these providers to understanding of meanings healthcare professionals assign to challenges they face, the successful practices they employ, and highlight opportunities for enhancement within geriatric care. Interpretative phenomenology influenced by Heidegger’s philosophy in qualitative research was conducted. Thirteen semi-structured interviews and narrative accounts with multidisciplinary healthcare providers from four Elderly Daycare Centres were collected and analysed, and interpretative phenomenological analysis (IPA). Multidisciplinary healthcare providers discovered four key aspects of their experience while delivering services in the first two programs (the Muscle Strengthening Program and the Nutrition Program for individuals with nutritional deficiencies): Opportunities in policy implementation, Challenging experience, Enhancing organisational effectiveness and engaging support, and Reflections on Program Outcomes and Impacts. All findings mirrored the value and impact of providing healthcare services in Elderly Daycare Centres on the experiences of healthcare providers from various disciplines. Elderly Daycare Centres not only provide healthcare services that offer emotional support but also positively influence seniors’ mental and physical well-being. Multidisciplinary healthcare providers caring for older adults encounter various experiences shaped by the complexities of aging populations. Support of this nature will heighten awareness of the difficulties elderly individuals encounter and advance potential solutions. Therefore, healthcare professionals stressed the need for a more holistic and coordinated care framework to improve both the delivery of services and health outcomes for elderly individuals.